Perkembangan Psikomotorik Bayi 6 – 9 Bulan berdasarkan Pemberian ASI Eksklusif - Agus Hendra Al-Rahmad; Ika Fadillah (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2016)
The growth of childhood starting from conception until the age of 18 years. The excellent quality child should be prepared as early as possible, one of them through exclusive breastfeeding, up to the age of 5 months 29 days, so that the growth and development of psychomotor perfectly. This study aims to measure the difference in motor development in infants exclusively breastfed to those not exclusively breastfed. The study was the cross-sectional study conducted in Batoh, July 2016. Samples were infants aged 6-9 months as many as 76. The collection of data is done using a form of SBC observation and interviewing the respondents. Analysis of data using Man-Whitney test Test at CI: 95%. The results showed 48,9% of infants were breastfed exclusively had a good score motor development (9,0), and showed a significant difference (p-value <0,05) than motor development in infants who are not exclusively breastfed, with a value of p = 0,000. In conclusion, the baby did not get a chance to experience exclusive breastfeeding psychomotor development standard below the average of two (2) times greater than being exclusively breastfed. Expected mothers to breastfeed their babies exclusively for a better psychomotor development. Keywords: Growth and development, psychomotor, exclusive breastfeeding, infants 6-9 months